Morbid obesity is not a contraindication to transport on extracorporeal support. (14th December 2017) - Salna, Michael; Chicotka, Scott; Biscotti, Mauer; Agerstrand, Cara; Liou, Peter; Brodie, Daniel; Bacchetta, Matthew
Abstract: OBJECTIVES: Extracorporeal membrane oxygenation (ECMO) transport has not been described in morbidly obese patients, a population that can pose significant challenges in obtaining vascular access, indexed flows and transport logistics. We sought to study the feasibility and safety of transporting obese and morbidly obese patients during extracorporeal support. METHODS: We conducted a retrospective review of all patients transported to our institution while receiving ECMO from September 2008 to September 2016. Survival to decannulation and survival to discharge were the primary outcomes. Obesity and morbid obesity were defined as a body mass index of greater than 30 kg/m 2 and greater than 40 kg/m 2, respectively. RESULTS: From 2008 to 2016, 222 patients were transported to our institution while receiving ECMO. Among these included patients, 131 were non-obese (interquartile range 22–27 kg/m 2 ), 63 were obese (interquartile range 31–35 kg/m 2 ) and 28 were morbidly obese (interquartile range 41–49 kg/m 2 ), with 6 patients having a body mass index greater than 50 kg/m 2 (range 52.3–79 kg/m 2 ). Pre-ECMO arterial blood gases, disease severity indices, cannulation strategies and transport distances were similar between these 3 groups. There was no mortality of patients during transport, and survival to discharge was 66% ( n  = 87) in non-obese patients, 56% ( n  = 35) in obese patients and 82% ( n  = 23) in morbidly obese patients ( P  = 0.042). On multivariable logistic regression analysis, body mass index was not a predictor of in-hospital mortality (odds ratio 0.99, 95% confidence interval 0.95–1.03; P  = 0.517). CONCLUSIONS: Transport of morbidly obese patients receiving ECMO may be performed safely and with excellent results in the setting of a dedicated ECMO transport programme with well-established management protocols.